2022
DOI: 10.1002/chem.202202207
|View full text |Cite
|
Sign up to set email alerts
|

Nonsymmetric [Pt(C^N*N′^C′)] Complexes: Aggregation‐Induced Emission in the Solid State and in Nanoparticles Tuned by Ligand Structure

Abstract: Five square-planar [Pt(C^N*N'^C')] complexes (Pt1-Pt5) with novel nonsymmetric tetradentate ligands (L1-L5) were synthesized and characterized. Varying the structure of the metalating aromatic systems result in substantial changes in photophysical properties and intermolecular interaction mode of the complexes in solution and in solid state. The complexes are strongly emissive in tetrahydrofuran solution, with the band maxima ranging from 560 to 690 nm. Three of these complexes (Pt1, Pt2, Pt4) afford nanospeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…2C). 56 In the same year, Zhang et al reported a rigid oxygen-bridged p -menthane-modified tetradentate cyclometalated platinum( ii ) complex ( Pt12 ). 16 Pt12 exhibited significant aggregation-enhanced emission (AEE) in a DMSO/H 2 O mixture (5 × 10 −5 mol L −1 ) with a high PLQY of 73.2%.…”
Section: Platinum Complexes With Aggregation-induced Emissionmentioning
confidence: 99%
“…2C). 56 In the same year, Zhang et al reported a rigid oxygen-bridged p -menthane-modified tetradentate cyclometalated platinum( ii ) complex ( Pt12 ). 16 Pt12 exhibited significant aggregation-enhanced emission (AEE) in a DMSO/H 2 O mixture (5 × 10 −5 mol L −1 ) with a high PLQY of 73.2%.…”
Section: Platinum Complexes With Aggregation-induced Emissionmentioning
confidence: 99%
“…Compound 8 was prepared following a slightly modified published procedure. 39 To a solution of bromopyrimidine 6 (139 mg, 0.35 mmol) and N-phenylpyridin-2-amine (51 mg, 0.30 mmol) in toluene (8 mL), t-BuOK (45 mg, 0.4 mmol), dppf (11 mg, 20 µmol) and Pd 2 (dba) 3 (9.2 mg, 10 µmol) were added under an Ar atmosphere. The reaction mixture was stirred at for 1 d at 110 °C (oil-bath temperature).…”
Section: Papermentioning
confidence: 99%
“…The synthesis of asymmetric CˆN*NˆC-coordinated yet non-mesogenic Pt(II) complexes was recently reported by Tunik et al, but without studying the effect of fluorination and chain length on the thermodynamics of aggregation while using orthogonal phenyl moieties at the bridging N-atom. [20] Herein, the photophysics of the six resulting complexes were studied by steady-state and time-resolved photoluminesce spectroscopy. To gain a deeper understanding of the excited-state properties, time-dependent density functional theory (TD-DFT) calculations were performed.…”
Section: Introductionmentioning
confidence: 99%